A History of Commissions: Threads of An Ottawa Planning History - Hillis, Ken (Urban History Review / Revue d'histoire urbaine, 1992)
Early planning in Ottawa takes the form of a piece-meal architectural admixture. On paper there remains a series of largely unrealized proposals designed to promote an image symbolic of national identity. Successive federal and municipal agencies worked to various degrees of success to augment Ottawa's appearance and amenity. British planner Thomas Adams' departure from, and the subsequent demise of the Federal Commission of Conservation in the early 1920's marked a low point in efforts to evolve comprehensive planning strategies. The career of Noulan Cauchon, first head of the Ottawa Town Planning Commission, aimed to keep the notion of planning alive in the city. Certain of his little-acknowledged proposals bear remarkable similarity to the pre-W.W. II planning efforts of MacKenzie King and Jacques Greber. Cauchon's legacy endures in proposals which appear to have been incorporated into federal planning activities during the post-war era.